2013
DOI: 10.5586/aa.2003.006
|View full text |Cite
|
Sign up to set email alerts
|

Relation between tipburn appearance of Chinese cabbage and calcium content and location

Abstract: In 2000-2001 investigations were carried out on the dependence between the tipburn appearance on Chinese cabbage and the content of calcium and its distribution in leaves. It was found that the highest concentration of calcium (to 4,4%) occurred in outside leaves and the lowest was found in leaves inside the head (to 1,0 %). The marginal part in every outside leaf contained more calcium than midrib of leaf. This dependence weakly appeared in leaves wrapping the head and was absent inside the head, where often… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…A tipburn injury appears on young leaves that contain lower level of calcium than the oldest leaves. This fact was demonstrated by Barta and Tibbitts (2003) with lettuce and Chinese cabbage (Borkowski & Kowalczyk 2003;Hernandez et al 2004). Borkowski and Kowalczyk (2003) have found that the youngest leaves inside the head contain 7.1-10.9 g Ca•kg -1 of dry matter and the old leaves 29.9-44.7 g Ca•kg -1 of dry matter.…”
Section: Discussionmentioning
confidence: 71%
See 4 more Smart Citations
“…A tipburn injury appears on young leaves that contain lower level of calcium than the oldest leaves. This fact was demonstrated by Barta and Tibbitts (2003) with lettuce and Chinese cabbage (Borkowski & Kowalczyk 2003;Hernandez et al 2004). Borkowski and Kowalczyk (2003) have found that the youngest leaves inside the head contain 7.1-10.9 g Ca•kg -1 of dry matter and the old leaves 29.9-44.7 g Ca•kg -1 of dry matter.…”
Section: Discussionmentioning
confidence: 71%
“…This fact was demonstrated by Barta and Tibbitts (2003) with lettuce and Chinese cabbage (Borkowski & Kowalczyk 2003;Hernandez et al 2004). Borkowski and Kowalczyk (2003) have found that the youngest leaves inside the head contain 7.1-10.9 g Ca•kg -1 of dry matter and the old leaves 29.9-44.7 g Ca•kg -1 of dry matter. These authors demonstrated that cultivars sensitive and cultivars tolerant to tipburn contained similar calcium content in leaves.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations